Pipe comb-tooth damage model caused by nozzle diversion block. (March 2022) - Zhao, Zhiyang; Song, Renbo; Cai, Changhong; Guo, Ke
Graphical abstract: Highlights: Deflected diversion with section-reducing causes fluid front fluctuation. Comb-tooth damage cause micro-ditches by fluid front fluctuation effect there. Based on average damage, the increases at micro-ditches or intervals are inverse. Deflection and acceleration behaviors redistribute fluid front damage ability. Separating section-reducing and diversion zones can distinctly avoid serious damage. Abstract: Side perforated nozzles reducing diameter, subjected to variable-pressure fluids, become vulnerable components, during controlling the fluid direction and dispersion in industrial spray equipment. The damage behavior of certain 405 stainless steel nozzles was evaluated with the proposed damage model, self-excited flow parameter fluctuations causing comb-tooth damage model. The nozzle inner bottom and adjacent wall of the diversion cone were expanded as a nearly-circular section groove with dense parallel micro-ditches and an adjacent bright transition belt above the expanded groove. The investigation suggests a separation design of the oblique diversion deflecting and section reducing for avoiding this model damage.